Biophysical analysis of a lethal laminin alpha-1 mutation reveals altered self-interaction - Patel, Trushar R.; Nikodemus, Denise; Besong, Tabot M.D.; Reuten, Raphael; Meier, Markus; Harding, Stephen E.; Winzor, Donald J.; Koch, Manuel; Stetefeld, Jörg (Elsevier, 2016)
Laminins are key basement membrane molecules that influence several biological activities and are linked to a number of diseases. They are secreted as heterotrimeric proteins consisting of one α, one β, and one γ chain, followed by their assembly into a polymer-like sheet at the basement membrane. Using sedimentation velocity, dynamic light scattering, and surface plasmon resonance experiments, we studied self-association of three laminin (LM) N-terminal fragments α-1 (hLM α-1 N), α-5 (hLM α-5 N) and β-3 (hLM β-3 N) originating from the short arms of the human laminin αβγ heterotrimer. Corresponding studies of the hLM α-1 N C49S mutant, equivalent to the larval lethal C56S mutant in zebrafish, have shown that this mutation causes enhanced self-association behavior, an observation that provides a plausible explanation for the inability of laminin bearing this mutation to fulfill functional roles in vivo, and hence for the deleterious pathological consequences of the mutation on lens function.